The idea factory bell labs and the great age of American innovation - Gertner, Jon (Penguin Books, 2013)
Highlights achievements of Bell Labs as a leading innovator, exploring the role of its highly educated employees in developing new technologies while considering the qualities of companies where innovation and development are most successful